Clarke's alpha, beta, and zero components: A possible approach for the conceptual design of instrumentation compatible with IEEE Std. 1459-2000 - Eigeles Emanuel, Alexander; Milanez, Dalgerti Lelis (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This paper explains the conceptual design of instrumentation that measures electric quantities defined in the Std. 1459-2000. It is shown how the instantaneous-space-phasor approach, based on alpha, beta, 0 components, can be used to monitor electric energy flow, evaluate the utilization of transmission line, and quantify the level of harmonic pollution injected by nonlinear loads.
Keywords: harmonics; power definitions; power measurements; power quality; space phasor